PERAN PUSTAKAWAN PERPUSTAKAAN PERGURUAN TINGGI DALAM MENINGKATKAN PRESTASI BELAJAR MAHASISWA - Sutriono, Sutriono (Pustakaloka, 2013)
Library is a vital componen of education. University libraryideally is able to contribute quality of education. And library can create some positive activities, like information literacy skills, competition of writing article, competition of book review, it also can develop designing groups of community for reading lovers, studying for librarianship and many others. Those would increase motivation for students to develop their competence by learning based on library, but in fact that many higher education libraries nowdays in our country are not well activities in learning proses to support rising of academi achievment.